Implementation of Pancasila Value for Generation Z in Technology Development - Evelyn Angelita Pinondang Manurung; Maria Osmunda Eawea Monny (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2021)
As the ideology of Indonesia, the existence of Pancasila is not without any challenges. In the development of science and technology, the existence of Pancasila is full of struggles. One of the challenges is the rapid social development that have happened nowadays has brought some changes in social activities. These social changes are marked by the development of the generation based on the needs for science and technology. Generation Z nowadays is known as the most active in their activities that depends on the technology devices and for this reasons generation Z needs strong guidelines in utilizing it. The implementation Pancasila value for Generation Z must be in accordance with the needs of Generation Z that are vulnerable for the ethics and morality. The knowledge of Pancasila value with dynamic ways for Generation Z is important so the moral value in Pancasila can be reflected in the personality of Generation Z. The research aims to implement the value of Pancasila that is important for the development of generation Z in the rapid progress of technology nowadays. This research used qualitative method. The implementation of moral science and characters based on Pancasila for Generation Z should be dynamics in accordance with the development of technological era. The implementation of Pancasila value based on their needs and characters of Generation Z is an anticipative way so the value of believe in God, humanity, unity, democracy and social justice still exist and create young generation that have the moral value of Pancasila.